2014
DOI: 10.1371/journal.pone.0105391
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Mixed-Strategy-Based Iterative Logit Quantal Response Dynamics in Game Theory

Abstract: Using the Logit quantal response form as the response function in each step, the original definition of static quantal response equilibrium (QRE) is extended into an iterative evolution process. QREs remain as the fixed points of the dynamic process. However, depending on whether such fixed points are the long-term solutions of the dynamic process, they can be classified into stable (SQREs) and unstable (USQREs) equilibriums. This extension resembles the extension from static Nash equilibriums (NEs) to evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…“The QRE has been compared with experimental observation and generally provides a better fit to the data than the NE” [ 35 ]. On this basis, we decided to evaluate the model using our experimental data.…”
Section: Methodsmentioning
confidence: 99%
“…“The QRE has been compared with experimental observation and generally provides a better fit to the data than the NE” [ 35 ]. On this basis, we decided to evaluate the model using our experimental data.…”
Section: Methodsmentioning
confidence: 99%
“…However, in contrast to the classical Nash equilibrium, the definition of QRE assumes that participants strive for the best answer only in the probabilistic sense: the better the answer, the more likely the participant will choose it 38 , 39 . A comparison of the QRE with experimental data indicated that this approach provided a better fit than the Nash equilibrium 40 . In practice, the QRE is dependent upon employing logistic distribution.…”
Section: Modelmentioning
confidence: 99%
“…However, in contrast to the classical Nash equilibrium, the definition of QRE assumes that participants strive for the best answer only in the probabilistic sense: the better the answer, the more likely the participant will choose it 34,35 . The QRE was compared with experimental data, and determined that this approach provided better fit than the Nash equilibrium 36 . In practice, the QRE is built upon employing logistic distribution.…”
Section: Quantal Response Equilibrium (Qre)mentioning
confidence: 99%